HIGHER EDUCATION FUNDING: COMPARATIVE ANALYSIS OF PORTUGAL AND POLAND PUBLIC SYSTEMS - Danuta Dziawgo; Isidro Féria; Sandra Saúde (Copernican Journal of Finance & Accounting, 2017)
In Europe governments remain a primary funding source    for higher education institutions. In this context, reflections on higher education funding models have been discussing since knowledge has been increasingly perceived as an essential condition for economic growth and the creation of wealth. The aim of the elaboration is to draw attention to selected aspects of the problem be viewed as an important market concerning the number of citizens and the European Union membership. In the article description, comparison and case study methods were used.